Confronting the meat paradox in different cultural contexts: Reactions among Chinese and French participants. (1st January 2016) - Tian, Qirui; Hilton, Denis; Becker, Maja
Abstract: As a well-known source of nutrition and pleasure, meat plays an important role in most people's diet. However, awareness of the "meat paradox"–the association of liking to eat meat but not wanting to kill animals–often implies the experience of cognitive dissonance. In two studies, focusing on meat production and meat consumption respectively, we examined whether participants used reduction of willingness to eat meat and reduction of mind attribution to food animals as strategies to reduce cognitive dissonance from the meat paradox in the Chinese and French cultural contexts. Focusing on meat production (slaughtering of an animal to produce meat; Study 1, n = 520), participants reported lower willingness to eat beef in a condition that emphasized the slaughter of a cow compared to a condition that presented a diagram of a cow as meat. In addition, French but not Chinese participants attributed less mind to cows when the relation between meat and its animal origin was made salient. Focusing on meat consumption (the transformation of meat into food; Study 2, n = 518), participants reported lower willingness to eat beef and attributed less mind to cows in a condition that emphasized the animal origin of meat compared to a condition that presented a recipe. These results suggest that the use of different strategies to resolve cognitive dissonance from the meat paradox depends on different contexts of the meat-animal link as well as on cultural context. Highlights: Participants' awareness of the meat-animal link was activated with pictures. Reducing willingness to eat meat was effective in resolving the meat paradox. Reducing mind attribution to cows was effective in resolving the meat paradox. The influence of meat paradox depends on culture and the kind of meat-animal link.